PENGARUH ADOPSI IFRS TERHADAP EARNINGS RESPONSE COEFFICIENT - , Arif Darmawan, Prof Dr. Zaki Baridwan, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
International Financial Reporting Standards (IFRS) is a lively debated issue in many countries. Different responses appear to respond to this issue, both supporting and opposing reaction IFRS adoption. Research on the impact of IFRS adoption is more focused on changes in the earnings component information for the assessment of the introduction of IFRS, but does not explain how the market reacts to earnings information. This study aims to determine whether adoption of IFRS will have a positive effect on earnings response coefficients of firms in Australia and the European Union and whether the information is supported by higher profit investors after the adoption of IFRS. By using a multiple regression analysis, this study shows that the application of IFRS, the quality of accounting information and responded positively by investors. Furthermore, the results of this study also shows that information to respond to a higher profit after adoption than before adoption of IFRS IFRS. These results are shown for EU countries + Australia and EU countries, but not for Australia.